On Kudriasov Conditions for Univalence of Integral Operators Defined by Generalized Bessel Functions - Mohsan Raza; Sarfraz Nawaz Malik; Qin Xin; Muhey U. Din; Luminiţa-Ioana Cotîrlă (Mathematics, 2022)
In this article, we studied the necessary conditions for the univalence of integral operators that involve two functions: the generalized Bessel function and a function from the well-known class of normalized analytic functions in the open unit disk. The main tools for our discussions were the Kudriasov conditions for the univalency of functions, as well as functional inequalities for the generalized Bessel functions. We included the conditions for the univalency of integral operators that involve Bessel, modified Bessel and spherical Bessel functions as special cases. Furthermore, we provided sufficient conditions for the integral operators that involve trigonometric, as well as hyperbolic, functions as an application of our results.